‘Physically efficient, psychologically detached’: prison healthcare staff experiences of, impacts from, and strategies for, working with prisoner self-harm and suicides - Hyde, Sara K S (2025)
This thesis has considered the experiences of prison healthcare staff working with prisoner suicide and self-harm in 21st century prisons in England and Wales. It was interested in temporality, in how these experiences impacted staff and their practice contemporaneously and over time, as well as how accumulation of such experiences affected them. It explored how healthcare staff may still deliver quality healthcare to those who are suicidal and self-harming, even in the context of ongoing prison crises.